The EDGE–CALIFA survey: validating stellar dynamical mass models with CO kinematics. Issue 1 (9th February 2018) - Leung, Gigi Y C; Leaman, Ryan; van de Ven, Glenn; Lyubenova, Mariya; Zhu, Ling; Bolatto, Alberto D; Falcón-Barroso, Jesus; Blitz, Leo; Dannerbauer, Helmut; Fisher, David B; Levy, Rebecca C; Sanchez, Sebastian F; et al.
Abstract: Deriving circular velocities of galaxies from stellar kinematics can provide an estimate of their total dynamical mass, provided a contribution from the velocity dispersion of the stars is taken into account. Molecular gas (e.g. CO), on the other hand, is a dynamically cold tracer and hence acts as an independent circular velocity estimate without needing such a correction. In this paper, we test the underlying assumptions of three commonly used dynamical models, deriving circular velocities from stellar kinematics of 54 galaxies (S0-Sd) that have observations of both stellar kinematics from the Calar Alto Legacy Integral Field Area (CALIFA) survey, and CO kinematics from the Extragalactic Database for Galaxy Evolution (EDGE) survey. We test the asymmetric drift correction (ADC) method, as well as Jeans, and Schwarzschild models. The three methods each reproduce the CO circular velocity at 1 R e to within 10 per cent. All three methods show larger scatter (up to 20 per cent) in the inner regions ( R  < 0.4 R e ) that may be due to an increasingly spherical mass distribution (which is not captured by the thin disc assumption in ADC), or non-constant stellar M/L ratios (for both the JAM and Schwarzschild models). This homogeneous analysis of stellar and gaseous kinematics validates that all three models can recover M dyn at 1 R e to better than 20 per cent, but users should be mindful of scatter in the inner regions where some assumptions may break down.